Suicide a growing problem - Abd Razak, Dzulkifli (2004)
WITH the launching of the suicide awareness month, Malaysia has now recognized that suicide is here to stay. Recent instances involving cases of youth taking their own lives confirm that this problem must be quickly tackled. A 1999 study of the pattern of suicides by the Kuala Lumpur Hospital shows some pattern, with the suicide rate among the Indians the highest (21.1 per 100,000).